Real-world operation of multiple sclerosis centres in Central-Eastern European countries covering 107 million inhabitants - Kokas, Zsófia; Járdánházy, Anett; Sandi, Dániel; Biernacki, Tamás; Fricska-Nagy, Zsanett; Füvesi, Judit; Bartosik-Psujek, Halina; Kes, Vanja Basic; Berger, Thomas; Berthele, Achim; Drulovic, Jelena; Hemmer, Bernhard; et al. (Multiple sclerosis and related disorders, 2023)
BACKGROUND: In 2018 multiple sclerosis (MS) care unit (MSCU) recommendations were defined. Nevertheless, the information on MS care, and whether MS centres fulfil the international recommendation is limited. Thus our objectives were to assess whether centres meet the MSCU recommendations and gain a comprehensive overview of MS care in Central-Eastern European countries. METHODS: A self-report questionnaire assessing aspects of the MSCU recommendations, disease-modifying therapy (DMT) and registry use and the patient number was assembled and sent to nine Central-Eastern European countries. Furthermore, one Danish and one German centre were contacted as a reference. RESULTS: In 9/9 countries, MS care was pursued in centres by MS neurologists and MS nurses. In Austria and the Czech Republic, management of MS was conducted under strict regulations displaying a referral centre system, fundamentally similar to but independent of the MSCU criteria. Several centres fulfilled all aspects of the MSCU criteria, while others had similar insufficiencies consisting of a speech therapist, continence, pain and spasticity specialist, neuro-ophthalmologist, and oto-neurologist. In 9/9 countries, DMTs were reimbursed. However, some centres did not provide every available DMT. A national registry was available in 4/9 countries with mandatory registry use only in Austria and the Czech Republic. CONCLUSION: In countries where MSCU recommendations are not fulfilled, a strictly regulated centre system similar to the Austrian and Czech model with a registry-based quality control might ensure appropriate care for people with MS.
Keywords: Česká republika; Epidemiology; Central-Eastern Europe; průzkumy a dotazníky; lidé; Multiple Sclerosis; Europe; Evropa; Neurology; Multiple sclerosis; Registry; Surveys and Questionnaires; Czech Republic; Disease modifying therapy; roztroušená skleróza; neurologie; Humans